2016
DOI: 10.1089/pop.2015.0097
|View full text |Cite
|
Sign up to set email alerts
|

The Core of Care Management: The Role of Authentic Relationships in Caring for Patients with Frequent Hospitalizations

Abstract: In the movement to improve the health of patients with multiple chronic conditions and vulnerabilities, while reducing the need for hospitalizations, care management programs have garnered wide attention and support. The qualitative data presented in this paper sheds new light on key components of successful chronic care management programs. By going beyond a task- and temporal-based framework, this analysis identifies and defines the importance of “authentic healing relationships” in driving individual and sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 28 publications
(22 reference statements)
3
50
0
Order By: Relevance
“…These surveys would benefit from detailed questions on patients' perceived met and unmet primary care needs and whether ED visits are meeting their unmet primary care needs. Additional qualitative research can build on Camden Coalition findings regarding frequent healthcare users' perceptions of their PCP relationships and how these individuals characterize successful authentic healing relationships with their health care providers. Semistructured interviews or focus groups with frequent ED visitors could also illuminate the psychosocial and medical characteristics that influence their ED use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These surveys would benefit from detailed questions on patients' perceived met and unmet primary care needs and whether ED visits are meeting their unmet primary care needs. Additional qualitative research can build on Camden Coalition findings regarding frequent healthcare users' perceptions of their PCP relationships and how these individuals characterize successful authentic healing relationships with their health care providers. Semistructured interviews or focus groups with frequent ED visitors could also illuminate the psychosocial and medical characteristics that influence their ED use.…”
Section: Discussionmentioning
confidence: 99%
“…They described trusting, continuous relationships with their health care team as important . Another qualitative study of Camden Coalition participants found that they valued an authentic healing relationship characterized by sincerity and genuineness …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A qualitative study by Grinberg et al 41 on the key components of successful case management reported that the development of a healing relationship between clinicians and their patients was based on security, genuineness, and continuity of care. A nonrandomized but controlled study by Adam et al 42 demonstrated an improvement in patient well-being after the implementation of a case management intervention by an interdisciplinary care team.…”
Section: Findings In Contextmentioning
confidence: 99%
“…The qualitative study by Grinberg et al 41 similarly suggested that the healing relationship between clinicians and their patients, based on security, could motivate the patient to engage in self-management. Another study, by Chapman et al, 44 with 31 health care professionals demonstrated that case management met patient needs through patient education about selfmanagement of their conditions.…”
Section: Findings In Contextmentioning
confidence: 99%